Playing by the Rules: Agency Policy and Procedure in Service Experience of IPV Survivors. Issue 21 (November 2020) - Wood, Leila; Cook Heffron, Laurie; Voyles, Molly; Kulkarni, Shanti
More than 1, 800 programs exist in the United States, providing not only shelter but also transitional housing, advocacy and support, transportation, legal aid, and group and individual counseling for women who have experienced intimate partner violence (IPV). Shelter and transitional housing provide critical support for survivors, but have also been critiqued for having too many restrictive rules and code of conduct. More information is needed about the impact of rules and agency policy on women seeking services in IPV residential settings. This qualitative study explored the central research question, "How do rules shape IPV residential environment and survivor experiences in services?" Twenty-five women in four programs in two states who were currently residing in IPV residential services were interviewed about their experiences. Data were analyzed using grounded theory methods. Findings indicated rules affect individual survivors' and families' experiences and responses in services and of healing from IPV (micro), the relationships among residents and between residents and staff (mezzo), and participants' relationships with the agency as an institution and the help-seeking community (macro). An intriguing paradox is noted in that at their best, rules provide stability and motivation for some survivors. At their worst, rules create isolation and force exit from shelter into unsafe circumstances, causing a ripple effect of impact. Implications include the need to restructure rules and policies collaboratively with residents, and reduce the amount of rules used in services. Addressing rules will better enable IPV services to be survivor-centered and trauma-informed, ultimately increasing safety and healing.